Historic architecture in the Caribbean Islands - Crain, Edward E. (University Press of Florida, 1994)
"Well-illustrated general survey describes the historic architecture of the area constructed before WWII. Organizes architectural examples according to building types: residences, military facilities, public and institutional buildings, and religious buildings. Short introductory chapters and brief descriptions take into consideration influential factors such as geography, climate, early Amerindian occupation, European and African immigration, emancipation, and immigration from Asia"--Handbook of Latin American Studies, v. 58.